Ghostbuster—A Western Blot-Based Panel Method to Resolve False-Positive Brucellosis Serology Test Results - Borbála Bányász; József Antal; Béla Dénes (Microorganisms)
False-positive serologic results (FPSRs) of brucellosis occur from time to time in various livestock with all the consequences (quarantine, compulsory slaughter, etc.) that follow true-positive laboratory results. A method based on the Polyacrylamide Gel Electrophoresis/Western Blot of a protein panel for resolving the FPSRs in the diagnosis of brucellosis was developed. Within the context of limited positive serum sample availability in Europe, the method successfully discriminates Brucella-positive sera from samples containing antibodies raised against infections caused by other Gram-negative bacteria causing FPSRs. An average CV% of 1.36 was determined for both repeatability and reproducibility for the whole separation mw range, and the test achieved 1.00 Diagnostic Sensitivity and 1.00 Diagnostic Specificity. The method with pre-prepared WB panels provides a rapid (less than 3 h), easily standardizable, and validatable alternative to existing confirmation methods. The whole WB process of the Brucella proteins and the subsequent densitometry can be accomplished with commercially available equipment, ready-to-use reagents, and open-source software, providing cost-effectiveness. The results of this study could attract broader attention, since molecular species in the 35.0–75.0 kDa range can serve as antigens in Brucella serology and the same fraction can be considered in the development of synthetic Brucella vaccines.